A spotlight on the surfacing of self-management of employees with diabetes seen by professional nurses in selected occupational health clinics in Cape Town - Natalie Copeling; Karien Jooste (AOSIS, 2020)
Background: Diabetes is considered one of the largest global health challenges of this century and one of the top 10 causes of death across the world. Studies indicate an increased economic burden in relation to diabetes, not only on government revenue but also within private industries. Exploring the perceptions of employees with diabetes mellitus as related to their self-management practices could assist in encouraging behaviours that are associated with positive management outcomes. Aim: The purpose of this study was to explore and describe the perceptions of employees with diabetes mellitus, seen by professional nurses in selected occupational health clinics, about the self-management of their disease. Methods: A qualitative, exploratory, descriptive contextual design was followed through 17 individual interviews with 17 employees working in various industries in Cape Town, using a semi-structured interview schedule. Open coding of the data followed, and four themes emerged. Measures to ensure trustworthiness were also adhered to in the study, and approval for the study was granted. Results: The study findings gave insight into the manner in which employees perceived their behaviour changes in terms of their self-management practices. Various emotions were expressed by employees relating to the disease as well as the lifestyle adaptations required for self-management thereof. Employees noted that knowledge acquisition and greater understanding of the motivators for lifestyle changes could improve aspects of their day-to-day living as well as the disease outcomes. Conclusion: Employees expressed an awareness of the changes and lifestyle adaptations needed but found aspects thereof to be an ongoing challenge. The areas of challenge varied amongst employees. A consciousness of the possible consequences of poor self-management practices and self-modification behavior to address these was observed.